IMPLICATIONS OF CONCURRENT LOW MUSCLE AREA IN DETERMINING THE SIGNIFICANCE OF INTER-MUSCULAR FAT IN OLD ADULTS. (16th November 2018) - Farsijani, S; Cawthon, P; Santanasto, A; Goodpaster, B; Kritchevsky, S; Boudreau, R; Harris, T; Newman, A
Abstract: Fat "infiltration" in skeletal muscle is considered an important predictor of impaired muscle function in older adults. Muscle fat depots is seen in broad pathological conditions, from obesity (in which relatively preserved muscle tissue is "infiltrated" by fat) to cancer cachexia (in which muscle wasting is concurrent with fat "replacement" of the muscle). However, whether the importance of muscle fat depots varies by the amount of muscle present is unknown. Objective: In older adults, to determine whether the associations between mid-thigh inter-muscular fat area and anthropometric characteristics, physical function and health conditions vary by low or high mid-thigh muscle cross-sectional area. Design: Participants (n= 1903; age 74–85y; 52.2% women) from the Health ABC study, were categorized into four groups; high inter-muscular-fat with low vs. high muscle area (fat^H/muscle^L and fat^H/muscle^H) and low inter-muscular-fat with low vs. high muscle area (fat^L/muscle^L and fat^L/muscle^H) based on 2003–04 CT data. Body composition (DXA), physical function and metabolic profile were compared across groups. Results: Compared to fat^H/muscle^H group, individuals in fat^H/muscle^L had lower BMI, appendicular lean mass (aLM) and fat mass. They had experienced an accelerated aLM loss over the previous 5-yrs. In the presence of low muscle area, physical function outcomes were mainly determined by the muscle area, and not the inter-muscular fat. Fat^H/muscle^H group had a metabolic profile resembling metabolic syndrome;lower HDL, hyperglycemia (in women), and hypertriglyceridemia (in men) compared to fat^H/muscle^L group. Conclusions: The negative effects of inter-muscular fat in aging are greatly influenced by the presence of concurrent low muscle mass, sex and age.